2020
DOI: 10.1080/14756366.2020.1804899
|View full text |Cite
|
Sign up to set email alerts
|

Potential anti-neuroinflammatory NF-кB inhibitors based on 3,4-dihydronaphthalen-1(2H)-one derivatives

Abstract: Nuclear factor kappa B (NF-rB) inhibition represents a new therapeutic strategy for the treatment of neuroinflammatory diseases. In this study, a series of 3,4-dihydronaphthalen-1(2H)-one (DHN; 6a-n, 7a-c) derivatives were synthesised and characterised by NMR and HRMS. We assessed the toxicity and anti-neuroinflammatory properties of these compounds and found that 6m showed the greatest anti-neuroinflammatory properties, with relatively low toxicity. Specifically, 6m significantly reduced reactive oxygen speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…It exhibits a broad spectrum of anticancer and antimicrobial activity [ 14 , 15 , 16 , 17 , 18 , 19 ]. On the other hand, there are reports in the scientific literature about dihydronaphthalene showing biological activity [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…It exhibits a broad spectrum of anticancer and antimicrobial activity [ 14 , 15 , 16 , 17 , 18 , 19 ]. On the other hand, there are reports in the scientific literature about dihydronaphthalene showing biological activity [ 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…These macrophages secrete important transforming factors, cytokines, and chemokines to activate signaling molecules that induce the proliferation of tumor cells and increase the degree of tumor malignancy [ 41 43 ]. In the TIM of glioblastoma, M1-type microglia exert antitumor immune functions by producing proinflammatory cytokines [ 44 , 45 ] and transcription signals as well as STAT1 [ 46 48 ]. However, in the present study, we found that FNDC4 promoted only the proliferation of glioblastoma cells, the potential mechanism associated with which may be related to the observed inhibition of M1 macrophage polarization by exocrine FNDC4.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, activated microglia can produce reactive oxygen species (ROS), which may indirectly induce neuroinflammation by activating NF-κB [10,11]. Therefore, NF-κB inhibitor with anti-neuroinflammatory activity may represent a therapeutic option for the treatment of inflammatory neurodegenerative diseases [12][13][14].…”
Section: Methodsmentioning
confidence: 99%